Studies on hybrid seed production in tomato (Solanum lycopersicum) using exserted stigma line with seedling marker - K. PADMINI; A.T. SADASHIVA; K. BHANUPRAKASH; L.B. NAIK (Seed Research, 2026)
A field experiment was conducted to adopt different pollination methods to evaluate the efficiency of a exserted stigma line (female parent) for hybrid seed production in tomato (Solanum lycopersicum L.). There were significant differences for hybrid seed recovery among the treatments. Highly significant and maximum values were recorded in hand-pollination without emasculation during two years of study. Among natural cross-pollination treatments, maximum per cent hybrid seed recovery was observed in alternate row planting of parental lines in a 1:1 ratio. With regard to seed quality, non-significant differences were observed among treatments for germination, seedling length and vigour index.